Answer:
g = 3
Step-by-step explanation:
12−1−7−g=1
Step 1: Simplify both sides of the equation.
12−1−7−g=1
12+−1+−7+−g=1
(−g)+(12+−1+−7)=1(Combine Like Terms)
−g+4=1
−g+4=1
Step 2: Subtract 4 from both sides.
−g+4−4=1−4
−g=−3
Step 3: Divide both sides by -1.
−g
/−1
=
−3
/−1
g=3
Answer:
43
Step-by-step explanation:
The first three numbers are perfect squares:
9 = 3²
16 = 4²
25 = 5²
43 is not a perfect square.
Answer:
90
Step-by-step explanation:
Mean:
(88 + 88 + 88 + 87 + 84 + 97 + 95)/7
627/7
89.57
90
Answer: im kinda losing brain cells rn
Step-by-step explanation: